2019
DOI: 10.1063/1.5079421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular discovery of half-metallic one-dimensional metal-organic framework

Abstract: Paper published as part of the special topic on Molecular Spintronics ARTICLES YOU MAY BE INTERESTED IN Two-dimensional self-assembly and electrical properties of the donor-acceptor tetrathiafulvalene-polychlorotriphenylmethyl radical on graphite substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Previous studies on half metal states in TM organic frameworks have also looked at the d-orbital occupation at different spin states. 21,22 In Table 1, we see that all TMs have a +2 oxidation state even though we calculated different CRR products for different TM atoms. Therefore, the oxidation states cannot explain the differences in the CRR activities of the TM–ZnS catalysts, which is different from the case of ZnO monolayers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies on half metal states in TM organic frameworks have also looked at the d-orbital occupation at different spin states. 21,22 In Table 1, we see that all TMs have a +2 oxidation state even though we calculated different CRR products for different TM atoms. Therefore, the oxidation states cannot explain the differences in the CRR activities of the TM–ZnS catalysts, which is different from the case of ZnO monolayers.…”
Section: Resultsmentioning
confidence: 97%
“…S8-S17 (ESI †), to assign the d-orbital occupation and the possible oxidation states for the TM atoms in TM-ZnS and TM-ZnO. We admit that there is arbitrariness in the assignments, and as mentioned in previous studies of TM-doped organic frameworks, 21 we can have states with mixed spin states. Thereby, the configurations given in Tables 1 and 2 are considered to be the dominant ones based on the PDOS given in the ESI.…”
Section: Tm-zns Properties and Stabilitymentioning
confidence: 89%
“…Recently, Marinescu and coworkers successfully synthesized a series of low-dimensional conductive transition-metal (TM)–dithiolene MOFs, which confirms the potential of MOFs as electrocatalysts for HERs. , The design of MOF electrocatalysts is based on the success of the cobalt–dithiolene monoanion as the homogeneous HER electrocatalyst. However, the performance of TM–dithiolene MOFs cannot compete with that using the state-of-the-art PGM-based electrocatalysts. , Thus the further optimization of TM–dithiolene MOFs as the HER catalysts is required. Previous theoretical studies suggest that the electronic properties of catalysts play critical roles in the determination of catalytic performance. Our recent studies revealed that the electronic properties of low-dimensional TM–dithiolene MOFs can be greatly affected by the metal node . As such, the catalytic performance of TM–dithiolene MOFs is further optimized by tuning the composition of the metal node in this study by means of density functional theory (DFT) computations.…”
mentioning
confidence: 88%
“…24−28 Our recent studies revealed that the electronic properties of low-dimensional TM−dithiolene MOFs can be greatly affected by the metal node. 29 As such, the catalytic performance of TM−dithiolene MOFs is further optimized by tuning the composition of the metal node in this study by means of density functional theory (DFT) computations.…”
mentioning
confidence: 99%
“…Downes and Marinescu synthesized a one-dimensional cobalt dithiolene MOF, which displayed excellent resistance to acidic aqueous solutions. , Later, they also reported Fe- and Ni-based dithiolene MOFs for the hydrogen evolution in acidic solution . Our recent studies revealed that the low-dimensional first-row transition-metal (TM)-dithiolene MOFs have great electrical conductivities. Thus, these TM-dithiolene MOFs have a great potential for CER.…”
Section: Introductionmentioning
confidence: 99%